Determination of commodity characteristics of emulsion based on low-methoxylated pectin for dishes of the «Eat Healthy» system in the restaurant service - Nikitchina, Tatiana; Manoli, Tatiana; Lebedenko, Tetiana; Kozhevnikova, Viktoriia (Technology audit and production reserves, 2021)
The object of research is emulsions based on low-methoxylated apple pectin for dishes of the «Eat Healthy» system in the restaurant industry. The subject of the research is the commodity characteristics of emulsions for dishes of the «Eat Healthy» system. In the course of the study, methods were used to determine commodity characteristics based on sensory and physicochemical analysis. The proposed ingredient composition of emulsions based on low-methoxylated apple pectin makes it possible to form not only high consumer qualities, but also to provide the target product with functional health properties. The sorption activity of pectin makes it possible to bind and remove heavy metals, radionuclides from the body; removal of strontium isotopes has a high activity. As a highly hydrophilic, biocompatible biopolymer of plant origin, it provides a high viscosity of the structure at low concentrations, has a pronounced neutral, pleasant sour taste. Low-methoxylated apple pectin is one of the most common hydrocolloids, which is used in the technology of products with therapeutic, prophylactic, sorption, bactericidal properties. In addition, low-methoxylated pectin substances are a harmless and economical material, and can be considered as an alternative to antibiotics and synthetic preservatives to prevent bacterial spoilage and extend the shelf life of health food for public catering with high consumer properties. The influence of the technological properties of low-methoxylated pectin in the formation of commodity characteristics for food products based on emulsions in healthy food products of restaurant establishments of different styles and concepts has been determined. Samples of food emulsions were studied using different amounts of low-methoxylated pectin as a stabilizer to obtain a sedimentation-stable emulsion system. The use of low-methoxylated apple pectin in the composition of food emulsions increases the aggregate stability of the product, functional and merchandising characteristics. On the basis of a complex quality indicator, the optimal parameters of the emulsion formulation were determined. High-quality consumer characteristics are ensured due to the size of uronic particles up to 0.78–0.81 μm in size.